More than Counter-urbanisation: Migration to Popular and Less-popular Rural Areas in the Netherlands - Bijker, Rixt Anke; Haartsen, Tialda (Population space and place, 2012)
ABSTRACT Migration into rural areas in Western countries is often explained by the pull of the rural idyll for urban, middle‐class migrants. Although previous research has shown that this counter‐urbanisation model is insufficient to explain rural immigration in sparsely populated countries, this paper shows that also within core regions, more diverse conceptualisations of migration into rural areas are required. This is achieved by distinguishing popular, average, and less‐popular rural living areas in the northern Netherlands, on the basis of average house prices, and by analysing the migration flows to these areas. Data from Housing Research of the Netherlands demonstrate that popular rural areas attract more highly educated people and people moving from urban areas compared with less‐popular and average rural areas. For movers to less‐popular areas, being near to family and friends is more important. The characteristics of the movers to popular rural areas fit very well with the counter‐urbanisation story. Less‐popular rural areas in the Netherlands share personal reasons as an important motivation for in‐migration with more remote rural areas in Europe. This indicates that conceptualisations of periphery and remoteness have to be considered within the local, regional, and national context. Research into rural population change in both core regions and sparsely populated countries should consider these different contexts to be able to acknowledge the variety in the way amenities and peripherality are perceived by different groups of people. Copyright © 2011 John Wiley & Sons, Ltd.